2019
DOI: 10.3390/w11102072
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Uncertainty Related to Climate Change in the Assessment of Urban Flooding—A Case Study

Abstract: Recent studies have pointed out that climate change is likely to have important implications on the extent and frequency of flooding events. Indeed, the intensification of the water cycle occurring in different areas of the world can dramatically affect the incidence of extreme events and, consequently, the flow in rivers or artificial channels, increasing the probability of disastrous floods. In this context, the criteria for the assessment of flood risk need to be improved to take into account the variabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…According to a report by the United Nations Office for Disaster Risk Reduction (UNISDR), floods accounted for nearly half of all weather-related disasters, affecting approximately 2.30 billion people between 1995 and 2015 [4]. Due to global climate change, extreme rainfall and flooding events are becoming increasingly frequent in urban areas [5][6][7][8]. At nearly two-thirds of the world's rainfall stations, measurements are on the increase [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a report by the United Nations Office for Disaster Risk Reduction (UNISDR), floods accounted for nearly half of all weather-related disasters, affecting approximately 2.30 billion people between 1995 and 2015 [4]. Due to global climate change, extreme rainfall and flooding events are becoming increasingly frequent in urban areas [5][6][7][8]. At nearly two-thirds of the world's rainfall stations, measurements are on the increase [5].…”
Section: Introductionmentioning
confidence: 99%
“…At nearly two-thirds of the world's rainfall stations, measurements are on the increase [5]. The extreme precipitation caused by climate change intensifies the magnitude of and susceptibility to flood events [8]. Moreover, growing populations and rising urbanization exacerbate the potential losses and damages caused by floods [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the SSP5-8.5 pathway in particular, the median of the distribution of adaptation costs when both sea-level and socioeconomic uncertainties are sampled is substantially higher than the estimated median costs when only one or the other set of uncertainties is sampled (Figure 4d). Importantly, when considering the prevalence of using several cases (often quantiles) to represent uncertainty (e.g., Hinkel et al, 2014;Lincke & Hinkel, 2018;Liuzzo & Freni, 2019;Tiggeloven et al, 2020), it is prudent to compare the distribution of damages from the full sampling of both sea-level and socioeconomic uncertainties (Figure 4, gray distributions) and the three-percentile approach (Figure 4, black dots and whiskers). In absolute terms, using the three-percentile approach underestimates the 95th percentile of the distribution of NPV of adaptation costs by US$371 billion (SSP1-2.6), $906 billion (SSP2-4.5), $611 billion (SSP4-6.0), and $3 trillion (SSP5-8.5).…”
Section: Propagation Of Uncertaintymentioning
confidence: 99%
“…This method of using a few cases to characterize low‐, moderate‐, and high‐risk scenarios has the advantage of being computationally inexpensive and conceptually simple. Previous studies have leveraged this computational efficiency in assessing flood risks (e.g., Hinkel et al., 2014 ; Lincke & Hinkel, 2018 ; Liuzzo & Freni, 2019 ; Tiggeloven et al., 2020 ). However, previous work has also found that using only a point estimate of an exogenous model input can miss substantial variation (Sieg et al., 2019 ) and multimodality (Brown et al., 2015 ) in the distributions of outputs of interest, which can also lead to underestimating the probability of damaging floods (Zarekarizi et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%